TINJAUAN YURIDIS PUTUSAN MAHKAMAH KONSTITUSI TENTANG SISTEM PENDIDIKAN NASIONAL - yandi ugang (MORALITY: Jurnal Ilmu Hukum, 2017)
Abstract : This research to determine the considerations of Constitutional Court Justices in deciding related to the implementation of International School Stubs (RSBI) / International School (SBI), and to know the legal implications of the Constitutional Court decision on the implementation of International School Stubs (RSBI) International (SBI). Type of research used is research with normative and empirical approach, with data collecting technique that is library research and Field Research. The findings obtained from the results of research. Firstly, the decision of the Constitutional Court Number 5 / PUU-X / 2012 is wise with consideration of the implementation of RSBI contradictory to the 1945 Constitution of the Republic of Indonesia (NRI 1945) which could lead to, liberalization of education, the different treatment of access to education, also resulted in the commercialization of the education sector and the dualism of the education system potentially eliminating the national identity as opposed to the mandate of the 1945 Constitution of the Republic of Indonesia. Second, no longer RSBI / SBI in the national education system. However, there is no fundamental change post-verdict, because basically the school that gets permission penyenggaran RSBI / SBI is a quality school. The difference is simply no longer usingforeign languages as an introduction in learning and in the process of school administration no longer mention or use RSBI / SBI. The RSBI / SBI replacement teaching system will be planned when entering the new school year. Keywords : Decisions of the Constitutional Court, RSBI / SBI, Education